Transdisciplinary insight of digital architecture - Correia, R. (2022)
Considering the question of collaborative research in architecture with other arts and science, the research outlines a historic perspective of transdisciplinary digital architecture through the work of key personalities by establishing links between them. Researches on digital architecture history are generally grounded on methods with limited sets of primary sources and relevant data is overlooked. Following the increasing availability of digital data there are sources of information widely available on the internet, which have been previously ignored, and by using this new methodology they can be useful for scientific research, and specifically for this research. Data-driven and geospatial approaches can allow researchers to address multidimensional aspects. This paper presents the first preliminary results of an ongoing research.